2021
DOI: 10.48550/arxiv.2112.09337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cosmological constraints on the Multi Scalar Field Dark Matter model

Abstract: The main aim of this paper is to provide cosmological constraints on the Multi Scalar Field Dark Matter model (MSFDM), in which we assume the dark matter is made up of different ultra-light scalar fields. As a first approximation, we consider they are real and do not interact with each other. We study the equations for both the background and perturbations for N -fields and present the evolution of the density parameters, the mass power spectrum and the CMB spectrum. In particular, we focus on two scalar field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…On the other hand, the multi-field cosmology paradigm has proven to be an effective framework to account (in a single model) for several important characteristics/ingredients of the universe, e.g., early acceleration (inflation) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], dark matter [26][27][28], late acceleration [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. With respect to early and late acceleration, the crossing of the phantom divide line is a most wanted feature in scalar field cosmology; it has been shown that this crossing cannot be achieved by considering a single scalar field/fluid (unless stability is not demanded) [44].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the multi-field cosmology paradigm has proven to be an effective framework to account (in a single model) for several important characteristics/ingredients of the universe, e.g., early acceleration (inflation) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], dark matter [26][27][28], late acceleration [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. With respect to early and late acceleration, the crossing of the phantom divide line is a most wanted feature in scalar field cosmology; it has been shown that this crossing cannot be achieved by considering a single scalar field/fluid (unless stability is not demanded) [44].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the assumptions proposed give rise to many implications, and we would like to dwell on a few. It is worth to note that dark matter, made of several constituents, is already being actively studied [37,38].…”
Section: Introductionmentioning
confidence: 99%